Metabolomic analyses provide insights into the preharvest rind disorder in Satsuma Owari Mandarin - Pervaiz, Tariq; Park, Suejin; Rezk, Alaaeldin; Hur, Manhoi; Obenland, David; Arpaia, Mary Lu; El-kereamy, Ashraf (Frontiers in Plant Science, 2023)
Citrus fruit's appearance is the primary criterion used to assess its quality for the fresh market, hence the rind's condition is a crucial quality trait. Pre-harvest rind disorder is one of the major physiological problems in mandarins. The disorder occurs right before harvest following rain events in some Mandarin varieties. Despite the economic damage caused by this kind of disorder, very limited information is available about the molecular mechanisms underlying the occurrence of this disorder.In the present study, we evaluated the primary metabolites, antioxidants, and hormones associated with the pre-harvest rind disorder in Mandarins. The study was carried out using ten-year-old 'Owari' Satsuma mandarin trees grafted on 'Carrizo' rootstock and grown in a commercial orchard in San Joaquin Valley, California, USA. Samples were collected from healthy tissue of healthy fruit (HF_HT), healthy tissue of damaged fruit (DF_HT), and damaged tissue of damaged fruit (DF_DT). Damaged fruit (DF_HT and DF_DT) showed lower cellulose concentrations than healthy fruit tissues (HF_HT), however, had similar contents of pectin and hemicellulose. The antioxidant activities showed no significant difference in all paired comparisons between samples as expressed in the malondialdehyde (MDA) content. However, DF_DT had a higher H2O2 content compared to HF_HT, but DF_HT had a similar content to that of HF_HT. Furthermore, peroxidase (POD) and polyphenol oxidase (PPO) activities were increased in DF_DT compared to HF_HT (P = 0.0294) and DF_HT (P = 0.0044), This is a provisional file, not the final typeset article respectively. Targeted metabolomics analysis revealed that a total of 76 metabolites were identified in Satsuma rind tissues, and the relative concentrations of 43 metabolites were significantly different across studied samples. The hormonal analysis showed the involvement of jasmonate Omethyltransferase, jasmonic acid-amido synthetase JAR1-like, and JA-isoleucine may key role in causing the rind disorder in mandarins. In addition, the damaged fruit tissues have a higher level of jasmonic acid (JA), 12-oxo-phytodienoic acid, and JA-isoleucine than undamaged tissue.